Nest‐associated vocal behaviours of the south‐eastern red‐tailed black cockatoo, Calyptorhynchus banksii graptogyne, and the Kangaroo Island glossy black cockatoo, C. lathami halmaturinus. (14th June 2020) - Teixeira, Daniella; Hill, Richard; Barth, Michael; Maron, Martine; van Rensburg, Berndt J.
Abstract: Animal vocalisations can signify diverse behavioural contexts, knowledge of which can be applied in bioacoustic monitoring programs. Australia's endemic black cockatoos ( Calyptorhynchus sp., family Cacatuidae) are highly vocal species that are threatened in many locations. In this study, we describe the nest‐associated vocal behaviours of two endangered subspecies of black cockatoo, the south‐eastern red‐tailed black cockatoo, C. banksii graptogyne and the Kangaroo Island glossy black cockatoo, C. lathami halmaturinus . Breeding success is limiting their recoveries and nest monitoring is challenging, but vocal recordings might provide valuable long‐term information hard to obtain otherwise. We recorded daily vocal activity at wild nests of both cockatoos using autonomous sound recorders. Combined with behavioural observations and video footage, we identified vocalisations characteristic of six behavioural contexts at nests: birds in flight, while perched, during begging (adult females), during courtship displays (adult males), when entering or sitting near to the nest hollow entrance (adult females), and from nestlings. Linear discriminant analysis on 12 acoustic measurements correctly classified 58.4% of calls of the red‐tailed black cockatoo ( n  = 907 calls from eight nests) and 62.9% of calls of the glossy black cockatoo ( n  = 1632 calls from 11 nests). In both subspecies, the female nest call and nestling calls are the most conspicuous vocal indicators of active nesting, and therefore should be considered for their bioacoustic potential. Other adult vocalisations indicate a range of behavioural contexts that could be informative for monitoring nesting behaviour, and its association to habitat features, in these endangered subspecies. Abstract :